Preputial Reconstructive Surgery to Correct Traumatic Balanoposthitis Induced Paraphimosis in A Bull - Ahuja, A.; Kumar, A.; Sachin; Chauhan, M.; Sood, P.; Sharma, A. (The Indian Journal of Animal Reproduction, 2021)
A non-descript bull was presented with paraphimosis. Penile examination revealed severely edematous preputial sheath leading to preputial prolapse and a severely inflamed penis having single traumatic region in the middle of the shaft. After providing necessary medication, the bull was restrained and laid down in left lateral recumbency. The local infiltration of lignocaine hydrochloride and adrenaline was done around the proximal preputial sheath along with the orifice. A 1.2 cm long equilateral triangular portion (contralateral to the side of recumbency) on the free area of prepuce was carefully dissected, preventing the injury to peri-penile elastic layers. The apex of the dissected triangular portion pointed towards the root of the penis. Similar procedure was repeated on the other preputial side (left lateral) by laying the bull in right lateral recumbency. The sutures were removed two weeks after the surgery and bull recovered uneventfully.